Efficacy and safety of add-on Viola odorata L. in the treatment of COVID-19: A randomized double-blind controlled trial. (25th March 2023) - Adel Mehraban, Mohammad Sadegh; Shirzad, Meysam; Mohammad Taghizadeh Kashani, Leila; Ahmadian-Attari, Mohammad Mahdi; Safari, Ali Akbar; Ansari, Narges; Hatami, Hossein; Kamalinejad, Mohammad
Abstract: Ethnopharmacological relevance: Severe Acute Respiratory Syndrome (SARS) due to the novel coronavirus has become the highest priority that threatens human health. This situation demands widespread vaccination and the innovation of new therapeutic methods. Despite drug discoveries, the need for approving new medicaments is felt because of adverse effects and lack of efficacy. Several medicinal plants including Viola odorata L. are recommended in traditional Persian medicine for alleviating respiratory infection symptoms. Recent studies showed anti-inflammatory, antioxidant, anti-asthmatic, antitussive, analgesic, and antibacterial activities of sweet violet. These enhance respiratory functions, reduce pulmonary inflammation, and decline mucous membrane edema. This study aimed to evaluate the efficacy of sweet violet syrup in alleviating the manifestations of COVID-19 infection. Material and methods: A randomized parallel-group double-blind controlled trial was conducted at Al-Zahra general hospital, Isfahan, Iran. A total of 108 outpatients were enrolled in the study. The patients were randomly allocated to intervention and placebo groups, with 54 patients in each group. The allocation was concealed using sealed opaque envelopes. The intervention group received violet syrup and the control group received placebo syrup, an add-on to the conventional treatment. The outcomes were COVID-19 manifestations, such as dyspnea, cough, myalgia, headache, and diarrhea, considered as outcomes of the study and were evaluated twice using a visual analog scale before the intervention and after 7 days, at the end of the study. Patients were followed daily by phone calls to monitor proper drug consumption and possible side effects. Results: No significant difference was between groups regarding demographic characteristics and vital signs before and after the treatment. Although all symptoms have improved significantly in both groups, patients who received violet syrup recovered faster and the mean severity scores of cough (P = 0.025), myalgia (P = 0.036), headache (P = 0.037), and diarrhea (P = 0.044) decreased greater in comparison to control group. Conclusion: This study, the first clinical trial on the effectiveness of Viola odorata on SARS-CoV-2 patients, showed that Viola odorata L. effectively controls prevalent manifestations of COVID-19 including cough, myalgia, headache, and diarrhea. Regarding this survey, the violet syrup can be mentioned as a complementary treatment for viral influenza-like infections in which cough, myalgia, headache, and diarrhea are prominent. Graphical abstract: Image 1 Highlights: Viola odorata is recommended in Persian medicine for respiratory infection symptoms. This study showed that Viola odorata L. is effective in the treatment of COVID-19. The drug could relieve cough, myalgia, headache, and diarrhea in SARS-CoV-2 patients. Violet syrup had no side effects in COVID patients. It seems the drug subsides lung inflammation and reduces the disease progression.